La resa di alcuni semitismi sintattici indiretti nella versione gotica della Bibbia - Antonio Piras (Filologia Germanica, 2025)
The present study examines – in the light of the original Greek text – the rendering of the main syntactical Semitisms attested in the Gothic version of the Bible. The adopted solutions reveal a heterogeneous translation technique: the effort to render as faithfully as possible every original construction coexists with the attempt to achieve expressive freedom and stylistic variety. The analysis of such features confirms the principle already recognized in Greek and Latin Bible versions: Semitisms are not forced intrusions into the language system, but they tend to exploit pre- existent constructions that are mostly characterized by merely formal analogies.